Measurement based on engagement neuromarketing in online advertising communication in the private universities of the city of Huancayo 2018 - Vilca Rodríguez, Roy River (2020)
The research “Measurement based on the neuromarketing of engagement in online advertising communication in private universities in the city of Huancayo”, sought to determine the level of engagement in online advertising communication in private universities in the city of Huancayo. The methodology used is of a theoretical basic type, with a correlational descriptive level, the scientific method was used and with a simple descriptive transectional design. The level of engagement varies significantly, in the online advertising that the Universities implement, the Continental University is the one that reaches the highest level of engagement and the UPLA is the one that reaches the lowest level of engagement. Advertising images are key when generating positive engagement, undoubtedly through visual content you can establish emotional relationships, arouse customer curiosity is necessary. In the case of the Private Universities in Huancayo, only some are achieving it with some aspects such as experiences, activities, events and friendly language.